General, but not abdominal, overweight increases odds of asthma among Norwegian adolescents: the Young‐HUNT study. (10th September 2014) - Egan, Kathryn B.; Ettinger, Adrienne S.; DeWan, Andrew T.; Holford, Theodore R.; Holmen, Turid Lingaas; Bracken, Michael B.
Abstract Aim The aim of this analysis was to examine the association between asthma and general and abdominal weight status, defined by age‐ and sex‐specific cut‐offs for body mass index (BMI) and waist circumference (WC) in adolescents. Methods Participants aged 12–19 years in the Young‐HUNT (YH) Study (YH1 1995–1997: n = 8222; YH3 2006–2008: n = 7403) completed self‐administered questionnaires in school as part of a series of cross‐sectional, population‐based studies conducted in Nord‐Trøndelag, Norway. Weight, height and WC were measured. Adjusted odds ratios (ORs) and 95% Confidence Intervals (CI) for asthma, defined by self‐reported physician diagnosis, were calculated. Potential effect modifiers evaluated included sex and pubertal development status (PDS). Results Asthma was reported by 11.8% of the adolescents in YH1 and 17.0% in YH3. Asthma odds significantly increased for adolescents with general (OR = 1.33; 95%CI: 1.13, 1.56), but not abdominal, overweight and increased for adolescents with general (OR = 1.34; 95%CI: 1.02, 1.75) or abdominal obesity (OR = 1.36; 95%CI: 1.16, 1.60). Underweight had no association with asthma regardless of weight assessment type, and PDS did not meaningfully influence the associations between asthma and weight. Conclusion Overweight and obesity both increased the odds of asthma in 12–19 year‐old Norwegians. WC did not add further information to that already provided by BMI to improve our understanding of the association between asthma and weight.